Eyes Closing and Drowsiness in Human Subjects Decrease Baseline Galvanic Skin Response and Active Palmar Sweating: Relationship Between Galvanic Skin and Palmar Perspiration Responses - Momose, Hideya; Morimitsu, Norimasa; Ikeda, Eiji; Kanai, Shigeki; Sakaguchi, Masao; Ohhashi, Toshio (Frontiers in Physiology, 2020)
We previously constructed a perspiration ratemeter for the measurement of palmar sweating in human subjects. While, galvanic skin response (GSR) has been used to evaluate emotional responses in human subjects, however little is known relationships between the phasic and baseline components in GSR and active palmar sweating. From the above, we aimed to investigate the relationships in human subjects with handgrip exercise and eyes closing or opening. Fifteenth healthy volunteers (mean age: 26.9 + 8.7 years old) participated in the present experiments. We investigated the effects of maximal handgrip exercise, eyes closing or opening, and self-awareness of drowsy on the GSR, active palmar sweating, R-R interval in ECG, and percentage of α wave in EEG. The faster phasic component in GSR was completely agreed with the starting point of active palmar sweating. Handgrip exercise induced significantly faster spike in GSR, active palmar sweating and decrease in R-R interval in ECG. Eyes closing produced significant decreases in baseline GSR and active palmar sweating in all human subjects. The percentage of α wave in EEG also increased. In contrast, eyes opening increased significantly the baseline GSR and active palmar sweating. In the equivalent electrical model of human skin, the eyes closing-mediated time-dependent decrease in the baseline GSR is completely agreed with the hypothesis that the palmar skin voltage only in the model decreased time-dependently to 0.4 of the control during 6 min. The self-awareness of drowsy in mid-night working with computer produced similar decreases in baseline GSR and active palmar sweating to the responses with eyes closing in all human subjects. In conclusion, the faster spike in GSR was completely agreed with the starting point of active palmar sweating. Eyes closing and opening or self-awareness of drowsy produced significantly changes in baseline GSR and active palmar sweating, which may become useful tools for evaluating clearness or drowsiness in human subjects.